Preliminary experience of surgery after neoadjuvant immunotherapy combined with chemotherapy for stage-IIIB non-small cell lung cancer - Ding, Yizong; Zhao, Xiaojing; Christopoulos, Petros; Geraci, Travis C.; Fu, Yujie (Journal of thoracic disease, 2024)
Background: Previously, stage-IIIB non-small cell lung cancer (NSCLC) has been considered inoperable. In recent years, neoadjuvant immunotherapy has shown encouraging efficacy in the treatment of advanced stage NSCLC in several trials. However, the effectiveness and safety of neoadjuvant immunotherapy in treating stage-IIIB NSCLC are still unknown. Therefore, we conducted this retrospective study to examine the outcomes of surgery after neoadjuvant immunotherapy combined with chemotherapy for stage-IIIB NSCLC. Methods: Thirty patients with stage-IIIB NSCLC who were treated at the Department of Thoracic Surgery of Renji Hospital from January 2019 to September 2021 were analyzed retrospectively. Neoadjuvant immunotherapy combined with chemotherapy was administered prior to surgery. The curative effect was evaluated by imaging and pathological examinations. Results: The objective response rate (ORR) and disease control rate (DCR) of the patients after neoadjuvant therapy evaluated by imaging studies were 70% and 86.7%, respectively. Of the 30 patients, 19 (63%) underwent surgical resection, in which all achieved a complete R0 resection. The median operative time was 168 minutes (range, 75–295 minutes), and the average intraoperative blood loss was 215.3±258.4 mL. The median postoperative hospital stay was 8 days (range, 4–59 days). The major pathological response (MPR) rate was 73.7% (14/19), and the pathological complete response rate was 47.4% (9/19); 2/30 patients (6.7%) had postoperative complications, including two who developed bronchopleural fistulas and one mortality, from a postoperative pulmonary infection. The treatment-related adverse reactions were mainly grades 1–2. Only two patients had grade 3 anemia, and no grade 4 adverse reactions were observed. Conclusions: Neoadjuvant immunotherapy and chemotherapy combined with surgery in patients with stage-IIIB NSCLC is safe and feasible. The patient outcomes and optimal number of neoadjuvant treatment cycles need to be explored and studied further.